Effect of Deposit Mobilization and Credit Financing of Commercial Banks on Capital Formation in Nigeria - Jacob, Byyiyet Josiah; Ishaya, Yusha’u; Innocent, Idachaba Odekina (International Journal of Small and Medium Enterprises, 2019)
The low level of Capital formation in Nigeria has been blamed on the low level of savings occasioned by the low income level and high level of consumption which reduce the ability of banks to create money through intermediation. This study investigates the effect of deposit mobilization and credit financing of commercial banks on capital formation in Nigeria. Gross fixed capital formation was used as proxy for dependent variable, while credit to private sectors, lending rate and Total deposit liabilities were used as proxies of independent variables. The study employed time series quarterly data from Q1 1980 to Q4 2015, which constitutes 48 observations. Multiple regression techniques were used to analyze the data. The study found that (LRN and TDL) have positive impact on GFCF of Nigeria while credit to private sector has an inverse relationship with GDP. In view of this finding, the study recommended that Nigeria commercial banks should re-direct their intermediation activities effectively.JEL Classification: C22, C87, G2, G21, G29